Anticancer drugs associated with venous thromboembolic event: Analysis of the WHO pharmacovigilance database. - Silva, Angélique Da; Alexandre, Joachim; Lanéelle, Damien; Sassier, Marion; Chrétien, Basile; Fédrizzi, Sophie; Joly, Florence; Emile, George; Bertoletti, Laurent; Méry, Benoîte; Plane, Anne Flore; Legallois, Damien; et al. (Journal of Clinical Oncology, 2021)
3094 Background: Venous thromboembolic event (VTE) is a frequent complication of cancer, as of some classical cancer therapy, like chemotherapy and surgery. The advent of new therapies such as immunotherapy and targeted therapies has meant that new therapies may be associated with VTE. Reliable data concerning the association between ADs and VTE are scarce. Methods: On March 1st, 2020 we utilized VigiBase (International pharmacovigilance database) and performed a disproportionality analysis using reporting odds ratios (ROR) to determine the association between the 206 FDA- or EMA-labeled ADs and VTE, defined as deep vein thrombosis and pulmonary embolism. RORs were adjusted (aRORs) on population characteristics including the cancer risk of VTE with the primary tumor site according to Khorana classification and metastatic status. Results: A total of 50,438 VTE cases associated with at least one AD were identified. Thirteen ADs were associated with higher reporting of VTE of which 2 represented new VTE associations not previously confirmed in the summary of product characteristics or literature including sipuleucel-t and megestrol. ADs more reported with VTE were lenalidomide (n:5,796), bevacizumab (n:2,780) and thalidomide (n:1,700). ADs associated-VTE occurred mainly during the first 6 months after AD initiation. Conclusions: Although cancer itself may generate VTE, we identified 13 ADs associated with VTE overreporting. Recognition of AD most likely to cause VTE can help raise practitioner awareness and lead to earlier diagnosis and treatment. Futures studies should include ADs in VTE risk evaluation and evaluate the management of VTE when recurrences occur under AD favoring VTE. ClinicalTrial registration number: NCT04696250.